Evidence for an evolutionary relationship between the large adaptor nucleoporin Nup192 and karyopherins - Stuwe, Tobias; Lin, Daniel H.; Collins, Leslie N.; Hurt, Ed; Hoelz, André (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Nucleocytoplasmic transport is facilitated by nuclear pore complexes (NPCs), which are massive proteinaceous transport channels embedded in the nuclear envelope. Nup192 is a major component of an adaptor nucleoporin subcomplex proposed to link the NPC coat with the central transport channel. Here, we present the structure of the ∼110-kDa N-terminal domain (NTD) of Nup192 at 2.7-Å resolution. The structure reveals an open ring-shaped architecture composed of Huntingtin, EF3, PP2A, and TOR1 (HEAT) and Armadillo (ARM) repeats. A comparison of different conformations indicates that the NTD consists of two rigid halves connected by a flexible hinge. Unexpectedly, the two halves of the ring are structurally related to karyopherin-α (Kap-α) and β-karyopherin family members. Biochemically, we identify a conserved patch that binds an unstructured segment in Nup53 and show that a C-terminal tail region binds to a putative helical fragment in Nic96. The Nup53 segment that binds Nup192 is a classical nuclear localization-like sequence that interacts with Kap-α in a mutually exclusive and mechanistically distinct manner. The disruption of the Nup53 and Nic96 binding sites in vivo yields growth and mRNA export defects, revealing their critical role in proper NPC function. Surprisingly, both interactions are dispensable for NPC localization, suggesting that Nup192 possesses another nucleoporin interaction partner. These data indicate that the structured domains in the adaptor nucleoporin complex are held together by peptide interactions that resemble those found in karyopherin•cargo complexes and support the proposal that the adaptor nucleoporins arose from ancestral karyopherins.